Assessment of Students' Comprehension of Binary Concept Using Computer-Science-Unplugged-Method in a Selected Secondary School in Ilorin, Kwara State (Fountain Journal of Natural and Applied Sciences, 2018)
Computer-Science-Unplugged (C-S-Unplugged) is a method of teaching Computer Science in an interesting, engaging and entertaining way through collection of free learning activities without using a computer. Lack of computer facilities, inadequate computer systems and epileptic power supply in Nigerian Secondary Schools have deprived students of practical and hands-on activities. The C-S-Unplugged method can be used to teach computer studies concepts without using a computer. This study focused on assessment of students’ comprehension of Binary concept using the computer-science-unplugged approach in a selected Secondary School in Ilorin, Kwara State. The study investigated the students’ comprehension level of Binary concept using the C-S-Unplugged method performance test and determined students’ Self-Assessment of their learning with it. The researchers demonstrated the use of this method with the teaching of the Binary concept by engaging students in class activities to ensure that they understand the concept of this method and assess their comprehension level before attempting the survey. The study adopted a mixed method design, which comprised of one-short case pre-experimental design and descriptive research design of survey type. Fifteen Senior Secondary School One students were purposively selected as an intact class from the selected school. Mean, standard deviation and percentage values were used to answer the research questions, while t-test with value of 1.04 was used to test the only hypothesis: Ho1. There was no significant difference between male and female students’ self-assessment of learning with C-S-Unplugged method at 0.05 level of significance. These implied that students comprehended the Binary concept using this method and had a positive assessment of their learning with it. There were no gender differences on the students’ self-assessment using Statistical Product and Service Solution. It was recommended, among others, that secondary school teachers should employ the C-S-Unplugged method since the students enjoyed learning with it.Keywords: Game-based learning, C-S-Unplugged method, Binary Concept, Computer studies